Using the Excel Solver to Solve Linear Programming Problem of Work Shift Schedule - MOHD AZAHAR, NABIELA RAHAH; KAMARDAN, MUHAMAD GHAZALI (Enhanced Knowledge in Sciences and Technology, 2022)
Scheduling is important in every organization since it establishes order and flow, ensuring that all activities are completed on time. This study concentrates on a productive method for solving a labour scheduling problem found in a small-scale company, proposing the requirement of part-time labours in each shift, thus offering a logical way of managing these tasks and produce a new schedule each week, by virtue of changing demand for service while maximizing labour preferences. To deal with uncertainties arising from parameter estimates, an optimization approach based on linear programming is proposed. To address overstaffing and understaffing cases, the approach is evaluated using the Microsoft Excel solver. The results point to an optimum schedule that uses the solution to reduce the number of part-time employees on the payroll while simultaneously maximizing employee preferences, preventing the company from being understaffed and overstaffed on the weekends and weekdays.